Advances in the management of post-endodontic pain: a review - Varma, K Meghana; Kalyan Satish, Rajulapati; Sajjan, Girija S; Madhu Varma, K; Panitini, Bhavani; Ponnada, Naveena (International Journal of Dental Materials, 2023)
This review describes the management of post-endodontic pain pharmacologically and non-pharmacologically. Acute periapical inflammation brought on by endodontic treatment-related chemical, mechanical, and/or microbiological damage to the periapical region causes postoperative pain, which is multifactorial in nature. A wide range of technical and pharmacological techniques are taken into consideration and proposed to control post-operative endodontic pain, the present study primarily comprised an overview of systematic reviews, randomized clinical trials, and in vitro studies summarizing advancement in the management of post-operative endodontic pain.